Electroconductive Gelatin Methacryloyl-PEDOT:PSS Composite Hydrogels: Design, Synthesis, and Properties - Spencer, Andrew R; Primbetova, Asel; Koppes, Abigail N; Koppes, Ryan A; Fenniri, Hicham; Annabi, Nasim (ACS biomaterials science & engineering, 2018)
Electroconductive hydrogels are used in a wide range of biomedical applications, including electrodes for patient monitoring and electrotherapy, or as biosensors and electrochemical actuators. Approaches to design electroconductive hydrogels are often met with low biocompatibility and biodegradability, limiting their potential applications as biomaterials. In this study, composite hydrogels were prepared from a conducting polymer complex, poly(3,4-ethylenedioxythiophene):polystyrenesulfonate (PEDOT:PSS) dispersed within a photo-crosslinkable naturally derived hydrogel, gelatin methacryloyl (GelMA). To determine the impact of PEDOT:PSS loading on physical and microstructural properties and cellular responses, the electrical and mechanical properties, electrical properties, and biocompatibility of hydrogels loaded with 0-0.3% (w/v) PEDOT:PSS were evaluated and compared to GelMA control. Our results indicated that the properties of the hydrogels, such as mechanics, degradation, and swelling, could be tuned by changing the concentration of PEDOT:PSS. In particular, the impedance of hydrogels decreased from 449.0 kOhm for control GelMA to 281.2 and 261.0 kOhm for hydrogels containing 0.1% (w/v) and 0.3% (w/v) PEDOT:PSS at 1 Hz frequency, respectively. In addition, an experiment demonstrated that the threshold voltage to stimulate contraction in explanted abdominal tissue connected by the composite hydrogels decreased from 9.3 ± 1.2 V for GelMA to 6.7 ± 1.5 V and 4.0 ± 1.0 V for hydrogels containing 0.1% (w/v) and 0.3% (w/v) PEDOT:PSS, respectively. studies showed that composite hydrogels containing 0.1% (w/v) PEDOT:PSS supported the viability and spreading of C2C12 myoblasts, comparable to GelMA controls. These results indicate the potential of our composite hydrogel as an electroconductive biomaterial.